(untitled) (Indonesian Minority Justice Review, 2025)
This paper critically examines the legal dispossession of indigenous Papuan communities in Indonesia, focusing on the intersection of land rights and state-backed development projects. Despite constitutional guarantees of indigenous land rights, Papuans continue to face widespread land dispossession due to extractive industries, agricultural expansion, and infrastructure development. The study analyzes the legal mechanisms enabling this dispossession, particularly the 2004 Forestry Law, the 2007 Spatial Planning Law, and the 2012 Land Acquisition Law, and their role in facilitating state and corporate interests at the expense of indigenous populations. Through case studies of land conflicts in the Papuan region—especially those involving logging, mining, and plantation agriculture—the paper highlights the legal complexities and challenges in securing land rights for indigenous Papuans. The findings demonstrate that the legal system often prioritizes economic development over the protection of indigenous land rights, and that land disputes are frequently resolved in favor of corporate and state actors. The paper concludes by recommending legal reforms that ensure indigenous Papuan land rights are recognized and protected, including the strengthening of customary land tenure systems and greater involvement of indigenous communities in decision-making processes regarding land use.